Syntactic analysis of intra-sentential Arabic–English code-switching within verb phrase - Alazzam, Sakher Naji; Alamaren, Eman Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2022)
The current study aims at analyzing the syntax of Arabic-English intra-sentential code-switching within verb phrase boundaries and finding out how this type of code-switching is performed. Particularly, this study investigates the speakers’ maintenance of their Arabic syntactic structure ant word order while inserting English constituents at verb phrase level. In addition, it examines the effect of the originated patterns on Arabic structural rules and examines the validity of equivalence constraint provided by Poplack in Arabic-English intra-sentential code-switching. To this end, a qualitative approach is operated to gather the research data; the qualitative data are collected from Facebook chats and comments between Jordanian university students while they are communicating on Facebook. Then, conversational analysis technique is used to analyze the syntactic aspects of VP patterns of intra-sentential Arabic-English code-switching. Furthermore, clarification of some grammatical differences between Arabic and English is provided along with analysis. The findings showed that there are thirteen patterns performed within VPs despite the grammatical differences between the two languages. These patterns sometimes violate the grammatical rules of English. Meanwhile, the grammatical rules of Arabic are not affected by intra-sentential code-switching performed within VPs. That means Jordanian Arabic–English code-mixing violates the universal constraint of 'equivalence' proposed by Poplack (1980). The study provides a potential theoretical implication for the Arabic Language Academies in the Arab World by encouraging them to cooperate to carefully ponder the implications of this code-mixing, and they should coin Arabic words for all new English terms, especially those related to the technological and scientific innovations.